The effect of heat stress on some immune parameters of broiler chickens in the conditions of the Syrian coast - جزعه غيث; جبور زهير (Latakia University Journal -Biological Sciences Series, 2023)
The study was conducted on 180 one-day-old Ross hybrid chicks, without distinguishing between males and females, to determine the effect of heat stress on some immunological indicators. The chicks were divided into two groups, each group containing 90 chicks. The control group was under ideal temperature conditions suitable for broiler chickens throughout the experiment, while the heat stress group was subjected to heat stress from the age of 22 days to the age of 42 days for 7 hours a day during the day from ten in the morning until five in the evening at a temperature rate of 31 ± 1, with a relative humidity ranging between 70-80%, and a nursery density of 10 birds per square meter. The experiment lasted for six weeks, from 17/7/2022 to 28/8/2022. At the end of the experiment, at the age of 42 days, the white blood cell count and the weight of the liver and spleen were calculated for each group. The results showed a significant decrease (P<0.05) in the white blood cell count in the stress group (20.06±0.31) thousand cells/mm³ compared to the control sample (22.4±0.2) thousand cells/mm³, and a significant decrease (P<0.05) in the weight of the liver and spleen in the heat stress sample (33.6 ± 0.41, 1.88 ± 0.02) g, compared to the control group (38.7 ± 0.64, 2.24 ± 0.04) g.